Language switching may facilitate the processing of negative responses - Zang, Anqi; de Vega, Manuel; Fu, Yang; Wang, Huili; Beltrán, David (Frontiers in Psychology, 2022)
It has been proposed that processing sentential negation recruits the neural network of inhibitory control (de Vega et al., 2016; Beltrán et al. 2021). In addition, inhibition mechanisms also play a role in switching languages for bilinguals (Kroll et al. 2015). Since both processes may share inhibitory resources, the current study explored for the first time whether and how language-switching influences the processing of negation. To this end, two groups of Spanish-English bilinguals participated in an encoding-verification memory task. They read short stories involving the same two protagonists (Montse and Jordi), referring to their activities in four different scenarios in Spanish or English. Following each story, the participants received verification questions requiring “yes” or “no” responses depending on whether a given fact was correctly referred to one of the protagonists. Some of the verification questions were in the story's original language (non-switch condition) and others in the alternate language (switch condition). Results revealed that language-switching facilitated negative responses compared to affirmative responses, exclusively for questions switching from dominant language (L1) to non-dominant language (L2). This effect might reflect that the domain-general mechanisms of inhibitory control are recruited at least partially for both language switch and negation process simultaneously, although this phenomenon is modulated by language dominance.